2017
DOI: 10.3390/challe8020025
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Behaviour Change and Health Promotion

Abstract: Abstract:The evidence about the effectiveness of behaviour change approaches-what works and what does not work-is unclear. What we do know is that single interventions that target a specific behavioural risk have little impact on the determinants that actually cause poor health, especially for vulnerable people. This has not prevented health promoters from continuing to invest in behaviour change interventions which are widely used in a range of programs. The future of behaviour change and health promotion is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 7 publications
1
78
0
3
Order By: Relevance
“…The aim of education is to increase people's amount of knowledge and/or skills. To be effective, it needs to be more than simply about conveying information passively (Middleton et al, 2013;Laverack, 2017), such as experiential and social learning (Knowles, 1989;Dudley et al, 2015). It has been demonstrated that group-based interventions are more effective than individualbased ones, even when participants expressed their preference for individual treatments (Middleton et al, 2013).…”
Section: Redesigning Services and The Actors' Rolementioning
confidence: 99%
See 1 more Smart Citation
“…The aim of education is to increase people's amount of knowledge and/or skills. To be effective, it needs to be more than simply about conveying information passively (Middleton et al, 2013;Laverack, 2017), such as experiential and social learning (Knowles, 1989;Dudley et al, 2015). It has been demonstrated that group-based interventions are more effective than individualbased ones, even when participants expressed their preference for individual treatments (Middleton et al, 2013).…”
Section: Redesigning Services and The Actors' Rolementioning
confidence: 99%
“…Evidence on the effectiveness of the existing interventions aimed at changing individual behaviour is mixed (Davis et al, 2015;Matjasko et al, 2016;Laverack, 2017). There are concerns over the magnitude of the impact on populations as a whole and individual adherence to programmes, especially following the termination of interventions (Middleton et al, 2013;De Poli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interventions rely on active participation and participants that have a shared interest in the topic and cause are generally more active and engaged (Laverack, 2017). Adolescents can be seen as empowered rather than exploited when one listens to what they have to say, and whether they want to be included at all, by feeling that the issue is important and significant for them (Allard, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The added benefit of empowerment is that it provides the individuals with greater control in attaining healthy lifestyles that are sustainable (Laverack, 2017). According to Shier (2001), participation includes such aspects as listening to the adolescents, supporting them in expressing their views, taking the adolescents’ views into consideration, including them in decision-making processes, and sharing responsibility for decision-making with the adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of medical experts represents a big challenge for many countries. This problem was more evident in countries with large areas covered with natural hindrances, like mountains and deserts or islands [31]. In these countries, governments are significantly challenged to resolve these problems.…”
Section: Discussionmentioning
confidence: 99%